Economic and educational factors played roles in the development of regional vision impairment in Shandong province, China - Lizhen Han (Nature Portfolio, 2021)
Abstract We analyze regional factors and spatial distribution of children's vision impairment in Shandong province, to explore the spatial changes brought by time and their influencing factors, so as to provide scientific basis for prevention of childhood vision impairment. This study covers five complete cross-sectional surveys from 2013 to 2017, involving about 29.24 million students. Spatial autocorrelation and hotspot analysis methods were used to analyze spatial features. The associated factors were analyzed by multinomial logistic regression. The vision impairment prevalence showed a trend of decreasing first and then increasing from 2013 to 2017, with slight changes. In terms of regional spatial differences, Weihai and Yantai have the highest VI rates in all years, and there was a large-scale spatial aggregation phenomenon. The southern low-value clusters, however, showed a trend of weakening from year to year. Further exploration revealed that economic factors and number of full-time teachers were verified as risk factors for regional vision impairment levels. The slight rebound of the prevalence of vision impairment and the high rate in the eastern and northern regions of Shandong province need more attention. It is suggested that relevant departments should focus on the influence of regional economic and educational factors when formulating relevant strategies.